Integrative and Complementary Health Practices in Coping with the Covid-19 Pandemic Period by Remote Workers - Ribeiro, Nyna Teixeira; Oliveira, Giovanna Carvalho de; Nakashima, Yuri; Tomé, Lorena de Paula Fragoso; Durce, Karina (O Mundo da Saúde, 2023)
The Covid-19 pandemic brought challenges and adaptations to individuals' lifestyles, requiring strategies to prevent the disease, with isolation and social distancing, which included remote work (RW) and adaptation of the routine and occupational structure. This new dynamic had a biopsychosocial impact, reducing performance during work and generating physical, psychological and emotional problems. Given this context, it is necessary to investigate resources that minimize these impacts. The use of Integrative and Complementary Health Practices – ICHP was investigated as a resource to combat the Covid-19 pandemic by workers in remote activities. This was a cross-sectional study, carried out by applying a questionnaire, via the Google Forms tool, to individuals over 18 years of age who had been in remote occupational activities for at least 3 months during the Covid-19 pandemic. 186 individuals aged 20 to 70 years old, randomly selected by invitation on social networks, participated in the study, and they had to meet the inclusion criteria and could belong to different work sectors. Regarding the impact of the pandemic on health, the majority (40.32%) felt it was “reasonable”, while the impact of RW on health was reported by 37.63% as “not harmful”. 66.67% of participants did not practice any ICHP before the pandemic. Of these, 20.91% started some practice during isolation, 78.26% did more than one modality and 21.74% only one. The reasons reported for starting the practice were: pain and/or orthopedic injuries, anxiety and stress. The most common practices were: meditation (14.5%) and yoga (10.22%). For those who started some practice, the importance in relation to health was considered very important by 65.22% and when asked about the use of ICHP, as a strategy to face the pandemic, it was considered very important by 47.83%. It is concluded that PICS were resources considered important for health and sought after to combat the Covid-19 pandemic, by workers in RT, with meditation and yoga being the most used therapies.